2002
DOI: 10.1023/a:1014140104777
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cooled tip RF current delivery at high power is associated with increased myocardial lesion size which may facilitate successful ablation of ventricular tachycardia associated with acquired structural heart disease. Catheter-tip temperature should be maintained below 45 degrees C to prevent popping and abrupt impedance rise during RF energy delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It is associated with current delivery at high power and prolonging the duration of RF delivery in cooled tip RF [11]. Watanabe et al [4] reported that by using cooled tip, depth and volume of myocardial lesion were significantly larger in dogs. For creating a larger lesion with less accurate targeting, bipolar RF with water-cooled tip is advantageous in various procedures of pain management of severe degenerative changes or failed back surgery syndrome in which accurate placement of electrode is difficult [5,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with current delivery at high power and prolonging the duration of RF delivery in cooled tip RF [11]. Watanabe et al [4] reported that by using cooled tip, depth and volume of myocardial lesion were significantly larger in dogs. For creating a larger lesion with less accurate targeting, bipolar RF with water-cooled tip is advantageous in various procedures of pain management of severe degenerative changes or failed back surgery syndrome in which accurate placement of electrode is difficult [5,12].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, accurate prediction of lesion created by ablation is essential for less morbidity and more satisfying result especially in pain management. Water-cooled electrodes are capable of creating larger lesions than non cooled ones by removing heat from adjacent tissue and deliver power without causing high impedance and tissue charring [4]. By comparing the maximum surface area formed by conventional RF and cooled RF in egg white, these benefits of water-cooled RF could be specified.…”
Section: Introductionmentioning
confidence: 99%
“…These internally cooled radiofrequency electrodes act as heat sinks that remove heat from tissue adjacent to the electrode. Cooling can lead to larger lesions because it can remove heat from the tissue adjacent to the electrode tip, preventing charring of tissue and maintaining a low impedance to allow dissipation of heat to a larger area 7. As a result, lesions of a larger volume could be produced compared with noncooled electrodes 10,11.…”
Section: Methodsmentioning
confidence: 99%
“…Cooled radiofrequency is a novel technique whereby internally cooled radiofrequency probes can lead to larger lesions 7. By treating a greater area of tissue lateral to the posterior sacral foramina, the chance of disrupting the sacral lateral branches will be higher.…”
Section: Introductionmentioning
confidence: 99%
“…Design of the wet electrode enables perfusion of the hypertonic saline solution into the tumor region with uncontrollable and irregular enlarged treatment area [17,18]. Design of the cooled-tip electrodes allows circulation of the cooling agents inside the electrode, which helps lower the temperature on the contact surface, thus slows down local water loss rate, and eventually increases the coagulation volume up to 50% [19]. However there also exists regions with evaporation which blocks the RF energy transportation [20,21].…”
Section: Introductionmentioning
confidence: 99%